Evaluation of the Implementation of Mosquito Breeding Eradication (PSN) for Dengue Hemorrhagic Fever (DHF) in Elementary Schools in Pekalongan City - Opik Taufik; Budiyono Budiyono; Cahya Tri Purnami (GLOBAL HEALTH SCIENCE GROUP, 2025)
Dengue Hemorrhagic Fever (DHF) remains a public health issue in Pekalongan City, particularly among elementary school children. Mosquito Nest Eradication (PSN) is a key strategy in DHF control; however, cases are still being reported. This indicates challenges in PSN implementation and factors affecting its success. Objective to analyze the implementation of PSN in elementary schools and identify factors contributing to the persistence of DHF cases among elementary school children in Pekalongan City. A qualitative study with a case study approach was conducted, involving 20 participants. The primary informants included representatives from the Health Office, Education Office, school principals, teachers, and school health officers. Triangulation informants consisted of jumantik (mosquito monitoring) cadres, parents, and students. Data were collected through in-depth interviews, observations, and documentation.The data analysis followed a thematic analysis approach. First, all interviews were transcribed verbatim, and field notes from observations were reviewed. The data were then coded systematically to identify patterns and emerging themes. Codes were grouped into broader categories, and themes were refined through an iterative process. Triangulation was conducted by comparing data from different sources to enhance credibility and validity. Finally, findings were interpreted in relation to the study objectives, supported by direct quotes from participants to provide depth and context. PSN implementation in elementary schools in Pekalongan City has been carried out through activities such as draining water containers, covering potential mosquito breeding sites, and monitoring by health officers and school jumantik cadres. However, several challenges remain, including low community awareness of environmental cleanliness, lack of regular supervision in schools, and environmental and climatic factors that support mosquito breeding. Additionally, limited facilities and human resources in schools pose challenges to optimizing the PSN program. The implementation of PSN in elementary schools in Pekalongan City has been conducted but remains suboptimal, leading to the continued occurrence of DHF cases. Increasing community awareness, strengthening routine supervision in schools, and cross-sectoral support are needed to ensure the sustainability of the PSN program and reduce DHF incidence.